Mortality and missed opportunities along the pathway of care for ST-elevation myocardial infarction: a national cohort study - Clive Weston (European Heart Journal: Acute Cardiovascular Care, 2015)
In a cohort study of 112,286 patients with ST-elevation myocardial infarction (STEMI) surviving to hospital discharge between Jan 2007 and Dec 2010 A score was calculated for each patient based on the following components of care: pre-hospital ECG, acute use of aspirin, timely reperfusion, prescription at hospital discharge of aspirin, thienopyridine inhibitor, ACE-inhibitor (or equivalent), HMG-CoA reductase inhibitor and β-blocker, and referral for cardiac rehabilitation. In this way cumulative missed opportunities for care (CMOC) could be defined for each patient. Mixed-effects logistic regression models evaluated the effect of CMOC on risk-adjusted 30-day and 1-year mortality (RAMR).44.5% of patients were ineligible for one or more care component. Of patients eligible for all nine components, 50.6% missed one or more opportunity. Pre-hospital ECG and timely reperfusion were most frequently missed, predicting further missed care at discharge (pre-hospital ECG incident rate ratio [95% CI]: 1.64 [1.58–1.70]; timely reperfusion 9.94 [9.51–10.40]). Patients ineligible for care had higher RAMR than those eligible for care (30-days: 1.7% vs. 1.1%; 1-year: 8.6% vs. 5.2%), whilst those with no missed care had lower mortality than patients with ≥4 CMOC (30-days: 0.5% vs. 5.4%, adjusted OR (aOR) per CMOC group 1.22, 95% CI: 1.05–1.42; 1-year: 3.2% vs. 22.8%, aOR 1.23, 1.13–1.34).Opportunities for care in STEMI are commonly missed and significantly associated with early and later mortality.